2014
DOI: 10.1109/tpwrs.2013.2291378
|View full text |Cite
|
Sign up to set email alerts
|

Design of Anti-Windup Compensator for Energy Storage-Based Damping Controller to Enhance Power System Stability

Abstract: The application of energy storage (ES) in power system is limited due to the high cost of the ES device, which exponentially increases with its capacity. This paper is to improve the saturation-dependent stability of the power system equipped with the energy storage based damping controller (ESDC), and hence, reduce the required size of the ES. The phenomenon that the capacity of ES is smaller than the required value produced by the ESDC, is modeled as actuator saturation using the saturation function. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 32 publications
1
35
0
Order By: Relevance
“…In this subsection, the New England system [40][41][42][43][44] shown in Figure 8 is applied to demonstrate the effectiveness of the NSGC in a multi-machine power system. All the loads are considered as the constant impedance model.…”
Section: New England Systemmentioning
confidence: 99%
“…In this subsection, the New England system [40][41][42][43][44] shown in Figure 8 is applied to demonstrate the effectiveness of the NSGC in a multi-machine power system. All the loads are considered as the constant impedance model.…”
Section: New England Systemmentioning
confidence: 99%
“…The remaining issue is the design of an adaptive virtual control u r based on the approximate model (23).…”
Section: System Function Approximation Based On the Smooth Saturamentioning
confidence: 99%
“…Some studies have been reported in recent literatures [9][10][11][12][13][14][15]. In [11], the analysis and design of a BESS controller for a two-machine system are discussed and tested, but the analysis for general multi-machine systems is not comprehensively covered.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding robust control for damping oscillation by BESS, there are two mainstreams: linear and nonlinear robust control. In [14], the linear matrix inequality (LMI) method is used, which requires the solving of an optimization problem. In [15], the Port-Hamiltonian formulation and the related controller design method are applied on BESS to improve the transient stability.…”
Section: Introductionmentioning
confidence: 99%